Far‐Ultraviolet Photometric Characteristics of JSC‐1A and LMS‐1 Lunar Regolith Simulants: Comparative Investigations With Apollo 10084. Issue 11 (7th November 2022) - Gimar, C. J.; Raut, U.; Poston, M. J.; Stevanovic, A.; Protopapa, S.; Greathouse, T. K.; Retherford, K. D.; Friday, J. M.; Grimes, J. T.
Abstract: We have characterized the far‐ultraviolet (FUV) spectro‐photometric response of lunar soil simulants JSC‐1A and LMS‐1, reporting notable differences from our previous results for Apollo soil 10084 (Raut et al., 2018, https://doi.org/10.1029/2018JE005567 ). While JSC‐1A and LMS‐1 were designed to emulate the geotechnical and compositional properties of a low‐Ti and high‐Ti mare soil respectively, these terrestrial simulants lack "space weathering" attributes such as the nanophase iron present in the weathered rims of Apollo grains and glassy agglutinates. Photometric analyses of the JSC‐1A phase curves reveal a ∼3–4 fold increase in single scattering albedo (SSA) and a forward scattering behavior compared to 10084. LMS‐1 is shown to have SSA nearly twice that of 10084 and a near isotropic reflectance. Additionally, both JSC‐1A and LMS‐1 spectra present a blue slope in the FUV, with the JSC‐1A slope ∼10× larger than that reported for the 10084 soil. Our analyses imply that low‐Ti content corroborated using energy dispersive x‐ray spectroscopy, correlates to brighter FUV reflectance and a greater spectral blue slope for JSC‐1A, while space weathering components likely contribute to the backscattering of FUV light by the Apollo soil relative to both simulants. Further work with an extended set of Apollo soils is warranted to deconvolute the relative contributions of weathering and composition to their FUV spectro‐photometric response. Plain Language Summary: We compare the far‐ultraviolet (115–200 nm) reflectance properties of the lunar mare soil simulants JSC‐1A and LMS‐1 to that of Apollo soil 10084, a lunar mare soil collected by the Apollo 11 mission at Mare Tranquillitatis. The reflectance spectra of both simulants and the Apollo 10084 sample show a blue slope, meaning they reflect more light at shorter wavelengths. Previous studies have linked this blue slope in lunar soils to space weathering features, although our results point to other compositional differences such as titanium‐bearing mineral content influencing this phenomenon. JSC‐1A and LMS‐1 scatter far‐ultraviolet light either away from the direction of incidence (forward scattering) or in all directions (isotropic), while Apollo 10084 scatters light toward the direction of incidence (backscattering). The backscattering observed in Apollo 10084 may be a result of nanophase iron generated in the exterior rims of the soil grains through the reduction of native iron oxide by solar wind and micrometeorites, a space weathering feature not present in the terrestrial simulants. Key Points: We compare far‐UV bidirectional reflectance of JSC‐1A, LMS‐1, and Apollo 10084 soil to deconvolute space weathering and composition effects JSC‐1A is brighter in the far‐UV and shows a steeper blue spectral slope than LMS‐1 and Apollo 10084, consistent with its low Ti content JSC‐1A and LMS‐1 mostly forward scatter in the far‐UV, likely from the absence of space weathering features in backscattering 10084 grains